Development and Economic Analysis of a Posture Correction Orthosis - Roman MURZAC; Cristian-Vasile DOICIN; Mihaela-Elena ULMEANU; Gabriela-Marina ENE (Communications of International Proceedings, 2020)
Early cost estimation is a common prerequisite for the profitability assessment of the development of complex products. Thus, the combination of numerous technical and economic factors poses a challenge for product developers when little more than the desired functionality of the product is known. In the field of medical devices, this issue is exacerbated by the fact that many devices should be custom products. The current research paper presents a detailed methodology for linking custom product architecture with cost analysis within the product design and development process for a posture correction orthosis. In order to make a cost estimation of hardware components for the posture correction orthosis, essential technical features and prices of typical components were identified via empirical research. The preceding selection of examined component categories was based on expert interviews, the analysis of finalized spinal orthosis projects and relevant literature. Several cost analyses were developed for each category of constructive solution. The most suitable constructive solution was chosen from these, based on their technical and economical characteristics. Nine constructive solutions for spinal orthoses were developed and several cost aggregates estimated using the presented method. The results were examined regarding their accomplishment of technical requirements and the value of estimated total cost. Costs were estimated for a built prototype that involved the chosen constructive solution shown in this study.
Keywords: Constructive Solutions; Product Architecture; Economic Analysis.